ChemInform Abstract: Gold‐Tin Ordering in SrAu2Sn2. Issue 41 (7th October 2014) - Schwickert, Christian; Gerke, Birgit; Poettgen, Rainer
Abstract The solid solutions SrAuxSn4‐x (1.7 ≤ x ≤ 2.2) are prepared by high‐frequency melting of the elements (Nb ampules, 950—1150 K, 2—12 h).